Forward guidance: Communication, commitment, or both? - Marco Bassetto (Institute for Fiscal Studies (IFS), 2019)
A policy of forward guidance has been suggested either as a form of commitment ("Odyssean") or as a way of conveying information to the public ("Delphic"). I analyze the strategic interaction between households and the central bank as a game in which the central bank can send messages to the public independently of its actions. In the absence of private information, the set of equilibrium payoffs is independent of the announcements of the central bank: forward guidance as a pure commitment mechanism is a redundant policy instrument. When private information is present, central bank communication can instead have social value. Forward guidance emerges as a natural communication strategy when the private information in the hands of the central bank concerns its own preferences or beliefs: while forward guidance per se is not a substitute for the central bank's commitment or credibility, it is an instrument that allows policymakers to leverage their credibility to convey valuable information about their future policy plans. It is in this context that "Odyssean forward guidance" can be understood.
Keywords: 330